2018
DOI: 10.1080/23744235.2018.1428823
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplantation for hepatic alveolar echinococcosis: literature review and three new cases

Abstract: LT combined with pre- and post-transplant benzimidazole therapy appears to be feasible and effective for patients with fatal HAE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Besides, achieving 2 cm resection margin for every single lesion is not possible in most advanced cases as recommended [3,4,28,30]. For excessive vascular in ltrated lesion or with severe comorbidities, only liver transplantation or ex vivo liver resection and autotransplantation could be selected from the perspective surgical treatment [11,[31][32][33][34][35][36][37][38][39][40]. Our data indicated that, different lesion types had different immune cell in ltrated belt.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, achieving 2 cm resection margin for every single lesion is not possible in most advanced cases as recommended [3,4,28,30]. For excessive vascular in ltrated lesion or with severe comorbidities, only liver transplantation or ex vivo liver resection and autotransplantation could be selected from the perspective surgical treatment [11,[31][32][33][34][35][36][37][38][39][40]. Our data indicated that, different lesion types had different immune cell in ltrated belt.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, achieving 2 cm resection margin for every single lesion is not possible in most advanced cases as recommended [3,4,28,30]. For excessive vascular infiltrated lesion or with severe comorbidities, only liver transplantation or ex vivo liver resection and autotransplantation could be selected from the perspective surgical treatment [11,[31][32][33][34][35][36][37][38][39][40]. Our data indicated that, different lesion types had different immune cell infiltrated belt.…”
Section: Discussionmentioning
confidence: 99%
“…Following this, medical treatment is continued for a while (12). Liver transplantation is a lifesaving in the treatment with hepatic hilum involvement, bile ducts and vascular invasion where liver resection or surgical treatment is difficult (13).…”
Section: Discussionmentioning
confidence: 99%